POLA SOSIALISASI NILAI-NILAI AGAMA DALAM KELUARGATERHADAP PERILAKU ANAK DI RW 5 KELURAHAN SUNGAI SALAK KECAMATAN TEMPULING KABUPATEN INDRAGIRI HILIR - Kurlillah, Aris; ", Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study was conducted to determine how the patterns of socialization that occurs, the values socialized and barriers that affect the process of socialization of religious values in the family in Sungai Salak Rw 5 Tempuling Indragiri Hilir subdistrict. Where in each pray, pray tarawih fewer children compared with adults or people tua.Untuk know the patterns of socialization that happens, religious values are socialized and constraints that affect the process of socialization hamatan Nili-religious values in the family in the Village Bark River District of Tempuling Indragiri Hilir, the authors conducted data collection by using the technique of guided interview with the respondent. The entire Muslim population of the community who have children aged 7-13 years. Total Penentruan samples using sampling techniques of data collection by way of the overall population sampled, sample 54 parents and 54 young respondents. Results of research conducted shows that of the pattern of authoritarian, democratic and permissive, permissive pattern is a pattern that many families used to educate children in the cultivation of religious values. Religious values in this study include the implementation of praying, reading the Qur'an (Koran), fasting Ramadan, the morality of the parents and other people or others can be said to be good. In accordance with the goal of planting religious values to children as a handle and guidance in carrying out the teachings of Islam. If viewed as a percentage of the number of poor in the implementation of the values of religion are also quite large. It is theoretically influenced by how socialization received by children in the family. Obstacles in the process of socialization of religious values in Rw 5 Sungai Salak Indaragiri Hilir District of Tempuling District, that is the pattern of behavior that is different for each child, the attitude of parents who are too harsh and discipline led to the child too passive, difficulties in communication, the environmental influences and technological progress is very rapid. Keywords : Socialization Patterns, Religious Values, Behaviors